1994
DOI: 10.1111/j.1095-8649.1994.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of algae by Stegastes nigricans and Amphiprion akindynos (Pisces: Pomacentridae), with an evaluation of methods used in digestibility studies

Abstract: An investigation of the digestive physiology of two species of damselfish (family Pomacentridae) was undertaken, comparing a herbivore Stegastes nigricans with an omnivore/ planktivore Amphiprion akindynos. Apparent digestibility of Enteromorpha flexuosa (Chlorophyta) was calculated using both total collection and a range of ash‐marker methods. In addition, Van Soest's system of fibre analysis was used to determine the digestibility of algal cell walls. A comparison of total collection methods (comparing food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
2
21
2
1
Order By: Relevance
“…Protein digestibility of macrophytes (LFec) in this study was similar to that found in Najas guadalupensis for T. zilli (75.1%) by Buddington (1979) and for the algae Enteromorpha for S. nigricans by Galetto & Bellwood (1994).…”
Section: Schizodon Borelliisupporting
confidence: 63%
See 2 more Smart Citations
“…Protein digestibility of macrophytes (LFec) in this study was similar to that found in Najas guadalupensis for T. zilli (75.1%) by Buddington (1979) and for the algae Enteromorpha for S. nigricans by Galetto & Bellwood (1994).…”
Section: Schizodon Borelliisupporting
confidence: 63%
“…Total diet ADCs, which recorded only plants (RIvi and Lfec), were lower than those found for cichlid Etroplus suratensis fed with Hydrilla verticellata (50-51.9%) by De Silva & Perera (1983), Tilapia nilotica fed with Cyanophyta (43%) by Moriarty & Moriarty (1973) and Stegaster nigricans fed with Enteromorpha algae (75%) by Galetto & Bellwood (1994). On the other hand, they were higher than those values reported by Buddington (1979) for T. zilli feeding on Najas guadalupensis (29.3%).…”
Section: Schizodon Borelliicontrasting
confidence: 45%
See 1 more Smart Citation
“…The assimilation efficiencies measured for both dusky and threespot damselfish fed artificial diets were higher than those reported for other pomacentrids feeding on algal foods (Lassuy 1984;Polunin 1988;Galetto and Bellwood 1994); this was clearly the result of an artificial diet formulated specifically for easy digestion. Nonetheless, on this diet threespot damselfish assimilated a larger fraction of the available protein than did dusky damselfish.…”
Section: Assimilation Efficiency and Intestine Lengthmentioning
confidence: 69%
“…We collected feces from individual fish prior to feeding every morning ($0830 hours) and afternoon ($1530 hours) for five consecutive days (Edwards and Horn 1982;Galetto and Bellwood 1994;Sturm and Horn 1998). Destructive sampling of fish for intestinal contents would have interfered with retention time experiments, thus we are unable to assess any leaching of nutrients from fecal material; however both species were held, and samples were taken, under the same conditions.…”
Section: Assimilation Efficiencymentioning
confidence: 99%